Genetics, environmental stress, and amino acid supplementation affect lactational performance via mTOR signaling pathway in bovine mammary epithelial cells - Li, Bin; Khan, Muhammad Zahoor; Khan, Ibrar Muhammad; Ullah, Qudrat; Cisang, Zhuo-Ma; Zhang, Nan; Wu, Dan; Huang, Bingjian; Ma, Yulin; Khan, Adnan; Jiang, Nan; Zahoor, Muhammad (Frontiers in Genetics, 2023)
Mammary glands are known for their ability to convert nutrients present in the blood into milk contents. In cows, milk synthesis and the proliferation of cow mammary epithelial cells (CMECs) are regulated by various factors, including nutrients such as amino acids and glucose, hormones, and environmental stress. Amino acids, in particular, play a crucial role in regulating cell proliferation and casein synthesis in mammalian epithelial cells, apart from being building blocks for protein synthesis. Studies have shown that environmental factors, particularly heat stress, can negatively impact milk production performance in dairy cattle. The mammalian target of rapamycin complex 1 (mTORC1) pathway is considered the primary signaling pathway involved in regulating cell proliferation and milk protein and fat synthesis in cow mammary epithelial cells in response to amino acids and heat stress. Given the significant role played by the mTORC signaling pathway in milk synthesis and cell proliferation, this article briefly discusses the main regulatory genes, the impact of amino acids and heat stress on milk production performance, and the regulation of mTORC signaling pathway in cow mammary epithelial cells.